Russell, Richard Rankin, ed. Martin McDonagh: A Casebook. London and New York: Routledge, 2007. 187 pp. - Szverle, Ilona (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Although Martin McDonagh has not published a new play since 2003, in terms of scholarship critics and scholars exploring his plays have been prolific. In 2006 The Theatre o f Martin McDonagh: A World o f Savage Stories was published—edited by Lilian Chambers and Eamonn Jordan (Dublin: Carysfort)—with two Hungarian contributions: Mária Kurdi’s “The Helen of Inishmaan Pegging Eggs: Gender, Sexuality and Violence,” and Péter P. Mtiller’s “Domesticating a Theatre of Cruelty: The Plays of Martin McDonagh on the Hungarian Stage.” A year later this collection was followed by a volume appearing in the A Casebook series. A Casebook is one of the series published by Routledge, which gathers essays focusing on the work of a particular playwright. Brian Friel, Samuel Beckett, Harold Pinter, Edward Albee, Joe Orton, and other remarkable dramatists have hallmarked this series so far and now Martin McDonagh has found his way into it.